Telephone nurses' strategies for managing difficult calls: A qualitative content analysis - Irene Eriksson; Marie Wilhsson; Therese Blom; Carina Broo Wahlström; Margaretha Larsson (Wiley, 2020)
Abstract Aim To describe telenurses' strategies for managing difficult calls. Background Telenursing is a growing and complex area and places great demands on telenurses' knowledge and skills and on their ability to communicate and listen. To become emotionally concerned is central to telenurses' experiences of difficult calls. Design A descriptive qualitative study. Methods The data were collected during February 2017 through individual interviews with 19 telenurses at call centres and primary healthcare centres. Data were analysed with qualitative content analysis. Result The analysis revealed an essential strategy illustrated by the theme "to be calm and secure in themselves." Further categories described telenurses' strategies to manage difficult calls, labelled as: "to show commitment and interest," "to have structure in the call and use support systems," "to pause the call" and "to reflect on difficult calls." The results show that telenurses need multiple strategies to help them to navigate difficult calls.